2008
DOI: 10.3168/jds.2007-0853
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hepatic Key Enzymes of Dairy Calves in Early Weaning Production Systems

Abstract: The objective of the present study was to describe plasma hormonal and metabolite profile and mRNA expression levels and activities of the enzymes pyruvate carboxylase (PC), phosphoenolpyruvate carboxykinase (PEPCK), and acetyl-coenzyme A (CoA) carboxylase in the liver of male Holstein calves before (1 and 3 wk of age) and after (8, 13, and 19 wk of age) weaning at 6 wk of age. The mean plasma concentration of acetate and beta-hydroxybutyrate increased, and that of plasma lactate and nonesterified fatty acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 38 publications
2
21
0
10
Order By: Relevance
“…There was an increase in serum glucose levels in both groups with increasing age (period effect, p<0.0001), in our earlier study (Lohakare et al, 2012). Haga et al (2008) reported that plasma glucose levels were lower around weaning (8 wk) but then increased at 13 and 19 wk of age that corresponds well with the present results. The weaning stress along with lower feed intake could be the reason for lower plasma glucose in both groups at this time period.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There was an increase in serum glucose levels in both groups with increasing age (period effect, p<0.0001), in our earlier study (Lohakare et al, 2012). Haga et al (2008) reported that plasma glucose levels were lower around weaning (8 wk) but then increased at 13 and 19 wk of age that corresponds well with the present results. The weaning stress along with lower feed intake could be the reason for lower plasma glucose in both groups at this time period.…”
Section: Discussionsupporting
confidence: 93%
“…Glucose serves as the main energy source in neonatal and pre-ruminant calves, but the lactose intake/milk intake does not meet glucose demands in very young calves (Girard et al, 1992). Also, the reduction in milk intake and the introduction of solid food cannot meet glucose demands; hence for carbohydrate homeostasis, glycogenolysis and gluconeogenesis become important in the liver (Girard et al, 1992; Hammon and Blum, 1998; Haga et al, 2008). Feeding and managing calves is expensive, requires extensive labour and contributes significantly to farm expenses.…”
Section: Introductionmentioning
confidence: 99%
“…metabolism of lactose, which after 60 days of fermentation was no longer detected. Although HAGA et al (2008) have reported that lactose is the main energy source for pre-ruminants, in this work we infer that the fat and lactic acid present in the silage are suffi cient to provide energy for animal growth. This was evident in the weight gain of the animals fed with colostrum silage which was higher than the recommended by NRC (2001).…”
Section: ------------------------------------------------------Days Omentioning
confidence: 71%
“…According to Haga et al (2008), the main energy source for young calves is glucose from lactose present in milk or milk replacer, however with advancing age and rumen development, glucose concentrations tend to decrease. Blood glucose values for calves vary from 80 to 120mg/ dL; however, diarrheic calves may have hypoglycemia due to anorexia, poor digestion and absorption and therefore reducing hepatic gluconeogenesis and increased anaerobic glycolysis.…”
Section: Discussionmentioning
confidence: 99%